Foot Anthropometric Measurements of Hong Kong Elderly: Implications for Footwear Design (Journal of Fiber Bioengineering and Informatics, 2016)
Degenerative changes and foot deformities are common when people get older. Foot deformities, such ashallux valgus, bunionettes and pes planus, are commonly found among older people, which may lead tochanges in foot anthropometry. A decline in functional mobility and greater risk of falling are linked tofoot deformities and footwear. This study therefore aims to evaluate the anthropometric measurementsbetween healthy and deformed feet in order to determine the key foot measurements in relation to thedeformed foot which can also act as indicators in current footwear sizing systems. By using a 3D hand-held scanner, 11 foot anthropometric measurements are captured and used to characterise the dimensionsand foot shape between healthy and deformed feet. A total of 49 elderly people between the ages of65-95 years old, including 41 women and 8 men (mean: 81.71; SD: 7.08) are recruited for this study. Theresults indicate that the foot characteristics of elderly people with foot deformities are different fromthose without deformities, especially in the larger deformity of the degree of hallux valgus and increasedwidth of the ball for women, and higher instep height for men. The length of the foot and ball, widthand girth of the ball, and degree of hallux valgus deformity are common predictors for differentiatingbetween healthy and deformed feet. It is also found that the current footwear sizing systems fail toaccommodate the foot dimensions of elderly people in both foot length and width, which may thereforelead to foot discomfort and even limit their daily life activities.
Keywords: Foot problems; Anthropometry; Footwear design; Elderly; 3D scanning